Losing Oneself and Finding the Other: A Response to Jonathan Silin. (March 2013) - Bansel, Peter
In responding to Jonathan Silin's article 'At a Loss: Scared and Excited', the author takes up his invitation to articulate a relationship between the personal and the professional, and contemplates the autobiographical as more than a mode of recounting one's own experience. In so doing he foregrounds possibilities for working with an autobiographical account of experience as both a self-reflexive research method and a site for learning about oneself and others. The author situates autobiography as a generative space in and from which one might theorise the self, with the express purpose of simultaneously understanding something of the other. He uses a personal experience of loss as an intellectual resource in order to theorise: the formation of the self in and over time and space; the normative practices through which selves and their experience are made intelligible and recognisable; the relational character of recognition; and the possibilities of narrative for developing an ethic of solicitude and care. In thinking what this theorising might mean for early childhood education he gives an account of the ontological, epistemological and pedagogical implications of loss.